Financial openness and energy structure transformation - Jia, Xianjun; Xu, Wenjing; Wang, Kaiyue (Frontiers in Environmental Science, 2024)
Energy structure transformation is the only way for China to achieve the "dual carbon" goal, and one of the difficulties faced by energy transformation is financing. In the context of China's steadily promoting the high-level opening-up of financial industry, this paper uses the panel data of China's provincial level from 2010 to 2019 to systematically examine the impact of financial opening-up on the transformation of energy structure. The results show that: (1) Financial openness has a significant positive impact on the energy structure transition; (2) In different stages of energy structure transformation, as the main driving force in the initial stage of energy structure transformation is the government's policy support, with the continuous maturity of energy structure transformation, the impact of financial openness on energy structure transformation gradually increases; (3) With different levels of economic development, the driving effect of financial openness is also different.The lower the level of economic development is, the stronger the driving effect of financial openness on energy structure transformation is due to the lack of financing channels. This paper provides a theoretical basis for China's energy structure transformation, and also provides rich policy implications for promoting China's financial industry to open up at a high level.